THE EFFECT OF TRANSFORMATIONAL LEADERSHIP STYLE ON JOB SATISFACTION AND ORGANIZATIONAL COMMITMENT TOWARDS ORGANIZATIONAL CITIZENSHIP BEHAVIOR (OCB) - Salsabila Ardian; Purnadi; Suyoto; Muchammad Agung Miftahudin (RADJA PUBLIKA, 2026)
The aim of this study is to examine the relationship between transformational leadership and Organizational Citizenship Behavior (OCB), job satisfaction and OCB, as well as organizational commitment and OCB. This study uses a quantitative approach with a purposive method, with 114 employees of PT. Perkebunan Nusantara I Regional 3 Kebun Semugih as respondents. Data were collected through explanatory questionnaires designed using a 5-point Likert scale. The analysis technique applied is partial least squares structural equation modeling (SEM-PLS), processed using smartpls version 3.0. The analysis stages include validity, reliability, and hypothesis testing. The independent variables consist of transformational leadership, job satisfaction, and organizational commitment, while OCB serves as the dependent variable. These findings reveal that transformational leadership, job satisfaction, and organizational commitment have a positive and significant effect on Organizational Citizenship Behavior (OCB). Theoretically, these results reinforce previous research showing that these three variables significantly contribute to the improvement of employees' OCB in smes. Practically, this study suggests that the leaders of PT. Perkebunan Nusantara 1 Regional 3 Kebun Semugih has a positive influence on the enhancement of transformational leadership, foster job satisfaction, and strengthen organizational commitment, thereby encouraging higher levels of OCB and improving employee performance.